Influence of Tool-Workpiece Interface on Surface Integrity after Turning - Dubec, Jaroslav; Neslusan, Miroslav; Micietova, Anna; Cillikova, Maria (Communications - Scientific letters of the University of Zilina, 2014)
This paper deals with influence of flank wear on decomposition of cutting force in turning roll bearing steel. The decomposition is carried out to evaluate the components of cutting force in the tool-chip as well as tool-workpiece interface. The decomposition enables evaluation of the shear and normal forces in the both interfaces. The results of experiments and the following calculations show that while conditions for chip separation in the tool-chip interface stay nearly untouched due to progressive development of flank wear, mechanical load of machined surface associated with components of cutting forces progressively increases with flank wear. The paper also reports about influence of flank wear on surface integrity expressed in such parameters as residual stresses, surface topography, structure transformation and microhardness.